AI-guided laser purification of human iPSC-derived cardiomyocytes for next-generation cardiac cell manufacturing - Prakaimuk Saraithong; Peyton Krajcarski; Yukako Kusaka; Moe Yamada; Junichi Matsumoto; Hailey Cunningham; Sama Salih; Darby Jones; Devika Baddhan; Christian Hausner; Justus Anumonwo; Anthony Rosenzweig; et al. (Communications Biology)
Abstract Current methods for producing cardiomyocytes from human induced pluripotent stem cells (hiPSCs) using 2D monolayer differentiation are often hampered by batch-to-batch variability and inefficient purification processes. Here, we introduce CM-AI, a novel artificial intelligence-guided laser cell processing platform designed for rapid, label-free purification of hiPSC-derived cardiomyocytes (hiPSC-CMs). This approach significantly reduces processing time without the need for chronic metabolic selection or antibody-based sorting. By integrating real-time cellular morphology analysis and targeted laser ablation, CM-AI selectively removes non-cardiomyocyte populations with high precision. This streamlined process preserves cardiomyocyte viability and function, offering a scalable and efficient solution for cardiac regenerative medicine, disease modeling, and drug discovery.